Determinación del índice de madurez de la Quinua (chenopodium quinoa) en el sector de Taniloma, Cantón Latacunga, Provincia Cotopaxi, 2017. - Sasig Tipantuña, Jessica Fernanda (2018)
The research project "Determination of the index maturity of quinoa (Chenopodium quinoa) in the sector of Taniloma, Canton Latacunga, Cotopaxi Province, 2017", had as objectives, determine the best maturity index and evaluate the best drying process. Two phases was carried out in this research: from the field was held in Barrio Taniloma, Eloy Alfaro Parish where counted the days when the plot obtained 80% flowering, 85% grain setting, 80% milky grain and 80% pasty grain; at the laboratory phase, the panicles were harvested in the different indixes maturity, from the grain setting to the 30 days that their physiological state lasts. The seed harvested from the treatments for drying was set at a temperature of 30 ° C for 5 hours in the electronic incubator until they reached 12% humidity. Data were recorded on the percentage of germination, weight, humidity, size and incidence of pests, diseases and physiopathies. The other treatment, without drying, was brought directly from the field and dried to the environment. An experimental design of DBCA with 12 treatments and 3 repetitions was applied. The factors to be evaluated were: maturity and drying index. The best treatment is c6s1 (set 30 days), (without drying), with 92.67% germinative power, with a humidity percentage of 14.63%, which is optimal for storage and at the same time is viable for germination according to studies already carried out and the grain size is 5 mm.; greater weight was obtained in c1s1 (initial setting of the grain), (without drying) with an average of 30.49 gr per plant. The crop yield obtained in the research is 1034 kg / ha. The treatment with lower valuation is c1s2 (initial setting), (drying), with 1.67% of germinative power, this value is not adequate for the seed to be viable, the average weight of 29.56 gr, with a percentage of humidity of 12% and the size of the grain is 0.1 mm. To avoid losses in harvest and post-harvest, harvest should be made when the crop reaches its physiological maturity (mature pasty grain), allowing the whole field to dry for 15 days on canvas, allowing the seeds to aerate, avoiding the loss of moisture, germinative power and size.